2015
DOI: 10.1007/s10681-015-1446-8
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing upland and lowland rice ecotypes by selective SSRs and their applications in molecular-assisted selection of rice drought resistance

Abstract: Upland and lowland rices (Oryza sativa) are the two most important rice ecotypes adapted to agricultural ecosystems of contrasting soil water conditions. Consequently, they have distinguished genetic features associated with drought resistance. As they are essential germplasm resources for breeding water-saving and drought-resistant rice, effective methods for discriminating rice ecotypes and evaluating their drought resistances are required. Five and three selective SSR loci respectively for japonica and indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…SMRT sequencing technology has been successfully applied to full-length transcriptome sequencing studies in animals, plants and insects 26 28 . Furthermore, full-length transcriptome sequences obtained using SMRT sequencing contain numerous EST SSRs 29 , 30 , which can be used for genetic analyses of the sequenced species and their related species, as well as for studies of conservation biology and molecular assisted breeding 23 , 31 , 32 . To the best of our knowledge, no full-length transcriptome sequence of P. catalpifolia has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…SMRT sequencing technology has been successfully applied to full-length transcriptome sequencing studies in animals, plants and insects 26 28 . Furthermore, full-length transcriptome sequences obtained using SMRT sequencing contain numerous EST SSRs 29 , 30 , which can be used for genetic analyses of the sequenced species and their related species, as well as for studies of conservation biology and molecular assisted breeding 23 , 31 , 32 . To the best of our knowledge, no full-length transcriptome sequence of P. catalpifolia has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Among morphological traits for drought resistance, such as root characteristics [ 45 ], leaf rolling [ 46 ] and ratio of shoot and root [ 47 ], root length and root thickness have been positively related to field drought resistance [ 48 , 49 ], implying that robust roots can be used to distinguish upland and lowland rice. Further genetic differentiation between upland and lowland rice was explored by simple sequence repeats (SSRs) located in expressed sequence tags (ESTs) isolated from rice in response to drought treatment [ 44 , 50 ]. These previous studies suggested that there was considerable morphologic and genetic differentiation between upland and lowland rice.…”
Section: Introductionmentioning
confidence: 99%
“…With prolonged growth in these particular habitats, rice cultivars form habitat-specific characteristics with complex internal and external perceptions and response mechanisms from natural selection (Uddin et al, 2016). Once they are exposed to an environment different from their original habitats, alternative strategies need to be employed to counteract the negative effects triggered by abiotic stresses to ensure normal plant development (Colmer, 2002;Xia et al, 2015). Thus, an increasing number of comparative studies have been performed among different rice cultivars to unravel underlying adaptive mechanisms in the last decade (Xia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%